KEKERASAN DALAM DUNIA PENDIDIKAN PRESPEKTIF HUKUM ISLAM DAN HUKUM POSITIF INDONESIA - Aidil Fitri; Yudi Fahrian (Justici, 2023)
ABSTRACT The world of education is continuously presented with various types of violence; after the family, the world of education should be a comfortable place, but in reality, numerous forms of violence occur there continuously. Whereas violence merely creates animosity and grudges, trauma, and several other unpleasant outcomes, Even with violence, it will impede the attainment of the intended educational objectives, as outlined in statute number 20 of 2003. “Within the context of teaching the nation's life, the purpose of national education is to foster the growth of skills and the formation of a national character and culture that are worthy of respect, strives to develop pupils' potential to become individuals who believe in and respect God Almighty, have noble character, are healthy, informed, capable, creative, independent, and become citizens of a democratic and accountable state.”. To achieve this objective, moral and moral standards must, of course, be a major concern; yet, education is not only the transmission of knowledge to educate the brain while ignoring morals and morals in softening the heart. Islam has clearly supplied direction in education, as has our nation, which continues to expand and strengthen its education system. While no normal person wishes for violence to occur, circumstances, scenarios, and the surrounding environment may swiftly alter a situation. For this reason, all parties strive ceaselessly to prevent a recurrence of violence in the realm of education, filling it with happiness and imprinting younger generation with a kind heart.